PEO and PEO-heparin modified surfaces for blood contacting applications - DU, Jun Ying (My University, 2001)
The synthesis and characterization of various thiolated polyethylene oxide (PEO) polymers constitute a significant part of the work, from linear PEOs with different molecular weights, and different end groups, to star-type, multiarmed PEOs, to linear PEOs in which one end bears a thiol group and the other a bioactive group. Different reaction protocols were used for the synthesis of the different PEOs. Terminal thiol groups were attached to PEO by reaction with mercaptoacetic acid or cystamine. Thiolated PEOs were chemisorbed to gold films deposited on polyurethane or silicon wafer substrates. Combinations of PEO and chain-end functionalized PEO were used to passivate the gold films and impart specific bioactivity respectively. The interactions of the modified surfaces with blood and blood proteins were investigated using radiolabeling, electrophoresis and immunoblotting methods. In measuring protein interactions with gold-based surfaces using radioiodine-labeling methods, it was found that the radioactive iodide ions (125 I- ) in the protein solution became bound to the surface along with the protein. Data on the adsorption of fibrinogen and albumin from buffer and plasma onto surfaces modified with different PEOs showed that adsorption decreased with increasing PEO molecular weight, irrespective of the group on the "outer" end of the PEO (hydroxyl or methoxyl). Surfaces were also prepared using PEO to which heparin was conjugated. Unfractionated heparin and low molecular weight heparin conjugated PEO were used to modify both gold and polyurethane surfaces. Both the passivation effect of PEO and the anticoagulant effect of heparin were found to be evident for these surfaces. (Abstract shortened by UMI.)
Keywords: Chemical Engineering; Chemical Engineering